2004
DOI: 10.1007/s00520-004-0618-1
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of peri-operative quality of life in patients undergoing surgery for gastrointestinal cancer

Abstract: The purpose of this study was to assess the pre- and postoperative quality of life (QOL) of patients with gastrointestinal cancer and to investigate the relationship between QOL and various psychological and clinical factors. Eighty-five patients who underwent surgery for gastrointestinal cancer and 26 control patients undergoing surgery for digestive diseases other than cancer were interviewed. Two tests were administered to assess QOL and psychological status respectively: the Japanese-language version of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
2

Year Published

2005
2005
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 35 publications
(4 reference statements)
3
19
2
Order By: Relevance
“…We previously investigated QOL for patients with gastrointestinal disease, including cancer, who underwent surgery, using EORTC QLQ-C30 (Matsushita, Matsushima, & Maruyama, 2004). The results support the current study in that emotional function was lowest before surgery and recovered as treatment progressed (before discharge and 6 months after discharge).…”
Section: Changes In Qol Over the Study Periodsupporting
confidence: 90%
“…We previously investigated QOL for patients with gastrointestinal disease, including cancer, who underwent surgery, using EORTC QLQ-C30 (Matsushita, Matsushima, & Maruyama, 2004). The results support the current study in that emotional function was lowest before surgery and recovered as treatment progressed (before discharge and 6 months after discharge).…”
Section: Changes In Qol Over the Study Periodsupporting
confidence: 90%
“…In addition to our study, de Liano et al stated that QOL had no relation with postoperative complications. However, Matsushita et al concluded that it negatively influences the physical functioning of gastrectomized patients after 6 months [14,17]. We have to note that women had higher scores almost in all functional and symptom’s scales dimensions.…”
Section: Discussionmentioning
confidence: 74%
“…Although the scales of the earlier-stage cases were a little bit higher, this study as well as Huang et al study [18] had not shown any significant differences between early and advanced cancer stages when at least 6 month had passed after surgical treatment. On the other hand, Matsushita et al found that patients in the later stage of gastric cancer had a significantly worse quality of life [17]. Furthermore, there is no single opinion about the influence of postoperative complications following total gastrectomy on QOL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pathological staging is an important prognostic factor for gastric cancer patients and had a negative correlation to QOL [17] . This study showed that the QOL of patients was positively correlated with pathological staging.…”
Section: Factors Affecting Quality Of Lifementioning
confidence: 99%